Shifts in attentional scope modulate event-related potentials evoked by reward. - Nadig, Ajay; Kelley, Nicholas J.; Pornpattananangkul, Narun; Glazer, James E.; Nusslock, Robin (Cognitive, Affective & Behavioral Neuroscience, 2019)
Emotions broaden or narrow the scope of attention in order to facilitate adaptive responses in threatening and rewarding contexts. In the current study, rather than asking how emotions influence attentional scope, we considered the possibility that the relationship between attentional breadth and emotion is bidirectional by asking whether shifts in attentional scope alter emotional processes using an event-related potential (ERP) paradigm. Participants (N = 30) completed a modified version of a Monetary Incentive Delay (MID) task, wherein their attention was either narrowed or broadened as they attempted to win rewards. Behaviorally, narrowing attention improved task performance in the form of reduced errors and increased monetary winnings. During cue processing, narrowing (compared to broadening) attention reduced the Cue-P3 (irrespective of cue type). During feedback processing, narrowing (compared to broadening) attention reduced the Feedback-P3 to monetary wins and increased the Feedback-P2 and the Feedback-P3 to monetary non-wins. Results highlight complexity and bidirectionality in the relationship between attentional scope and affective processes.